Hur kredithandläggare lantbruk i sina kreditgivningsstrategier beaktar den potentiella riskfaktorn att säkerheten i form av åkermark faller i värde - Wassberg, Olof; Åkerblom, Jesper (SLU/Dept. of Economics, 2011)
The increase in farmland value in Swedens plain areas is a well known fact in today's Swedish agricultural. In connection with the fluctuating prices of crops and inputs, are increasing the risk exposure to agriculture. The increased value of agricultural land has in Sweden over the years been due to a high demand for land that has existed and exists in Sweden. The increasing demand is linked to a structural rationalization of Swedish agriculture, leading to fewer and larger farm units (www, privataaffärer, Carl Johan Jurss).